Should healthcare organisations offer ongoing rehabilitation services for patients undergoing haematopoietic cell transplant? A narrative review. Issue 2 (6th January 2021) - Mohammed, Jaleel; Kabir, Russell; Bakhsh, Hadeel R.; Greenfield, Diana; Georgievna, Volkova Alisa; Bulińska, Aleksandra; Rai, Jayanti; Gonzales, Anne; Hashmi, Shahrukh K.
Abstract : Purpose: Hematopoietic stem cell transplant (HSCT) patients can suffer from long-term transplant-related complications that affect their quality of life and daily activities. This study, a narrative review, aims to report the impact of HCT complications, the benefits of rehabilitation intervention, the need for long-term care and highlights the research gap in clinical trials involving rehabilitation. Design/methodology/approach: A comprehensive search strategy was performed on several databases to look for relevant articles published from 1998 to 2018. Articles published in English with the following terms were used: hematopoietic stem cell transplant, chronic graft-versus-host disease, rehabilitation, exercise, physical therapy, occupational therapy. A patient/population, intervention, comparison, and outcomes (PICO) framework was employed to ensure that the search strategies were structured and precise. Study year, design, outcome, intervention, sample demographics, setting and study results were extracted. Findings: Of the 1, 411 records identified, 51 studies underwent title/abstract screening for appropriateness, 30 were reviewed in full, and 19 studies were included in the review. The review found that, for the majority of patients who underwent HSCT and developed treatment-related complications, rehabilitation exercises had a positive impact on their overall quality of life. However, exercise prescription in this patient group has not always reflected the scientific approach; there is a lack of high-quality clinical trials in general. The review also highlights the need to educate healthcare policymakers and insurance companies responsible for rationing services to recognise the importance of offering long-term follow-up care for this patient group, including rehabilitation services. Practical implications: A large number of HSCT patients require long-term follow-up from a multidisciplinary team, including rehabilitation specialists. It is important for healthcare policymakers and insurance companies to recognise this need and take the necessary steps to ensure that HSCT patients receive adequate long-term care. This paper also highlights the urgent need for high-quality rehabilitation trials to demonstrate the feasibility and importance of rehabilitation teams. Originality/value: Healthcare policymakers and insurance companies need to recognise that transplant patients need ongoing physiotherapy for early identification of any functional impairments and appropriate timely intervention.